Interpreting the story of the Shipwrecked Sailor - John Baines (1990)
The story of the Shipwrecked Sailor is a complex work of written literature that is based partly on esoteric knowledge. Its superficial presentation looks to folk and oral models in style, situation, anonymity, and treatment of character, making play with traditional and proverbial wisdom. It is not allegorical in any simple sense. The conception of the seventy-four forms of the sun god is encapsulated within the folk/oral treatment, while the deviant wisdom that offerings to the gods are pointless is relativized by being put forward by a god. The core narrative of the end of things is a myth that is linked to moralizing on a modest, domestic scale; this pairing has parallels in religious texts. All these meanings are organized within a cyclical form which exploits first-person narration for ironical effect. The text is not didactic in any simple sense, but has the unifying theme of experience and how it is confronted.